ANALYSIS OF THE CONCEPT OF PRANA DESCRIBED IN AYURVEDA IN LIGHT OF ITS CLINICAL APPLICATION - Rakesh Narayanan V; Isha Herswani (International Journal of Applied Ayurved Research, 2015)
There are two common gateways of human body which are responsible for both growth of physical body and development of disease. All the treatment therapies are also depends upon these two factors and involved to maintain their normal status. Apart from materialistic ap-proach, other mode of treatment is more attracts the people now a day’s especially suffering from those diseases which are kept in chronic and disorders group of disease. Owing to changing environment, quality of nourishment through the one factor is decreasing so there is need to enhance the other factor of growth to especially overcome to above discussing dis-ease which relates with approach of Prana.